Utilizing Artificial Intelligence Technologies in Saudi EFL Tertiary Level Classrooms - AbdAlgane, Mohammed; Othman, Khalid Abdurrahman Jabir (Journal of intercultural communication, 2023)
This study focuses on the employment of AI technology in regular, day-to-day activities, such as when Google Translate or Bing Translator are encouraged alongside various programs and applications. It also evaluates and empirically demonstrates the subjects of writing with AI technologies, computer-assisted language learning (CALL), machine translation (MT), and automatic evaluation systems (AESs) in order to offer solutions for enhanced communication training in Saudi Arabia's EFL system. Word tune is an artificial intelligence (AI)-driven writing assistant that can understand the writer's ideas and suggest alternative rewrites (e.g., shorten, expand). This program assists writers of English as a foreign language to maintain a steady flow and acquire useful English expressions. This research made use of questionnaires as a method for collecting data and then ran those responses through SPSS for analysis. The use of artificial intelligence (AI) technology in English as a foreign language (EFL) settings has been shown to facilitate the English language learning (ELT) process and to keep both teachers and students up to date on recent technological developments. This exploratory investigation demonstrated that all digital and AI-powered devices have the potential to assist in teaching and learning. Consequently, the pedagogical component of future education can be developed using an AI framework.